The effects of food neophobia and openness to different cultures on ethnic food consumption: the case of tourism students - Karacaoğlu, Sıla; Cankül, Duran (Anais Brasileiros de Estudos Turísticos, 2024)
Students who have the opportunity to intern and work in different sectors of an international industry such as tourism are often in environments with different, diverse and ethnic foods and are in contact with foreign colleagues and tourists. Moreover, these students will have careers in different fields of tourism in the future, work in various destinations around the world and serve tourists from different cultures. The objective of this study is to evaluate how food neophobia (FN) and openness to different cultures (ODC) influence the consumption of ethnic food among undergraduate students studying tourism in different professions, considering socio-demographic factors. In this scope, a questionnaire was administered online to 3rd and 4th year students studying at undergraduate level in tourism departments of different universities in Türkiye between February-June 2024 and a total of 425 people were reached. The main findings show that socio-demographic variables have various levels of influence on FN and ODC. In addition, the results indicate that students with FN are more cautious and closed to ethnic food consumption preferences, while students who are open to different cultures are more willing and open to ethnic food consumption preferences. In addition, it was determined that students at gastronomy and culinary arts departments had the lowest level of neophobia, while tourism guidance students had the highest level of neophobia. On the other hand, tourism guidance students had the highest level of ODC, while gastronomy and culinary arts students had the lowest level of ODC.